Islamic leadership and work-life balance: Impact on Generation Z performance - Setianingsih, Hesti Eka; Achsania, Hendratmi (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examines the impact of Islamic leadership styles, including transformational, transactional, and charismatic approaches, on Generation Z employees’ performance. Rooted in ethical and moral paradigms, Islamic leadership underscores principles that resonate with the importance of work-life balance, a key priority for Generation Z.Methodology – Adopting a quantitative research methodology, this study evaluates the mediating role of work-life balance and the moderating influence of Islamic work ethics on the interplay between leadership styles and employee performance. Data were gathered through structured questionnaires completed by 101 Generation Z employees across diverse organizational settings.Findings – The findings reveal that charismatic leadership significantly enhances employee performance, with Islamic work ethics serving as a crucial moderating factor that strengthens the relationship between charismatic leadership and work-life balance. Conversely, transformational and transactional leadership styles demonstrate no significant impact on performance, highlighting Generation Z's preference for flexible and relational leadership.Implications – These results provide valuable insights for organizations aiming to integrate Islamic values into their leadership frameworks, fostering a unified and performance-driven work environment tailored to the aspirations of the modern workforce.Originality – This study uniquely explores the impact of Islamic leadership styles on Generation Z employees, emphasizing their distinct work-life balance priorities. It also introduced Islamic work ethics as a moderating factor, offering fresh insights into culturally relevant leadership practices.